2014
DOI: 10.1111/tid.12186
|View full text |Cite
|
Sign up to set email alerts
|

Endemic fungal infections in solid organ and hematopoietic cell transplant recipients enrolled in the Transplant‐Associated Infection Surveillance Network (TRANSNET)

Abstract: Background Invasive fungal infections are a major cause of morbidity and mortality among solid organ transplant (SOT) and hematopoietic cell transplant (HCT) recipients, but few data have been reported on the epidemiology of endemic fungal infections in these populations. Methods Fifteen institutions belonging to the Transplant-Associated Infection Surveillance Network prospectively enrolled SOT and HCT recipients with histoplasmosis, blastomycosis, or coccidioidomycosis occurring between March 2001 and Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 25 publications
2
140
0
1
Order By: Relevance
“…36 One study evaluating a random sample of US Medicare data reported an incidence of 6.1 cases per 100,000 person-years in the Midwest during 1999 to 2008. 37 The actual burden in the United States is unknown outside of a few states because histoplasmosis is not nationally notifiable.…”
Section: Endemic Molds Histoplasma Capsulatummentioning
confidence: 99%
“…36 One study evaluating a random sample of US Medicare data reported an incidence of 6.1 cases per 100,000 person-years in the Midwest during 1999 to 2008. 37 The actual burden in the United States is unknown outside of a few states because histoplasmosis is not nationally notifiable.…”
Section: Endemic Molds Histoplasma Capsulatummentioning
confidence: 99%
“…Environmental exposure in endemic areas may precipitate coccidioidomycosis (southwestern United States) or histoplasmosis (Mississippi Valley), and travel history is helpful to document possible exposure to rare fungi [43].…”
Section: Opportunistic Infectionsmentioning
confidence: 99%
“…No large epidemiologic registry of endemic fungal pneumonia in HM patients exists, though smaller studies suggest that HM patients develop endemic fungal pneumonias substantially more often than the general population 4,10 , and that these infections are more likely to be severe and/or lethal 8 . Interestingly, Transplant-Associated Infection Surveillance Network (TRANSNET) data suggest a very low rate of endemic fungal pneumonias in HSCT patients, potentially due to aggressive exposure avoidance during peak vulnerability 11 .…”
Section: Microbial Epidemiologymentioning
confidence: 99%